Evaluating the association of adverse childhood experiences, mood and anxiety disorders, and suicidal ideation among behavioral health patients at a large federally qualified health center. - April Joy Damian (Public Library of Science (PLoS), 2021)
Although numerous studies have examined the relationship between adverse childhood experiences (ACEs) and suicide, research is needed that studies the effects of specific ACEs, including subclasses of ACEs, independent of the effect of other ACEs. We explored the relationship between ACEs and suicidal ideation (SI) with special attention to patterns according to generation cohort (millennials: 22-37 years old, generation X: 38-53 years old, and baby boomers: 54-72 years old), and assessed the extent to which mood and anxiety disorders account for the relationship between ACEs and suicidal ideation. Patients in behavioral healthcare services of a large federally qualified health center (n = 4,392) were assessed at baseline on ACEs, SI, and mood and anxiety disorders. Logistic regression modeling was used to examine the data. Emotional neglect was the strongest predictor of SI among Millennials (OR = 1.59), Generation X (OR = 1.81), and Baby Boomers (OR = 1.88) after controlling for mood and anxiety disorders, race/ethnicity, and gender. Findings suggest ACEs predict an increased likelihood of having SI over and above the influence of mood and anxiety disorders, in models adjusted for gender and race/ethnicity. Across generations, the association with suicidal ideation was strongest for any child abuse and neglect, but not for household dysfunction. The observed association of ACEs with suicidal ideation suggests that ACEs should be considered as a risk factor and incorporated into screening assessments for suicidal ideation. Lastly, additional research on the association of ACEs and suicidality in individuals not actively being managed in behavioral healthcare settings is also warranted.